Analysis of Financial Performance: Case Study of Pt. X Employee Cooperative - NUFUS, KHAYATUN; SUPRATIKTA, HADI; MUCHTAR, AWALUDDIN; SUNARSI, DENOK (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to determine the level of health, growth and business prospects of the employees of the PT. X cooperative. The results of this study indicate that employees of general health level PT. X are in the category "moderately healthy" obtaining the average score of 68.00. Based on the result of a common size analysis of the balance sheet and operating result for the 2014-2018 period, PT. X did not experience significant growth and was really stable. Although based on the analysis of the segment report, the multipurpose loan business is the business with the most prospects for development.RESUMEN Este estudio tiene como objetivo determinar el nivel de salud, crecimiento y perspectivas comerciales de los empleados de la cooperativa PT. X. Los resultados de este estudio indican que los trabajadores de nivel de salud general PT. X se encuentran en la categoría “moderadamente saludable” obteniendo la puntuación media de 68,00. Basado en el resultado de un análisis de tamaño común del balance general y resultado operativo para el período 2014-2018, PT. X no experimentó un crecimiento significativo y se mantuvo realmente estable. Si bien se basa en el análisis del informe de segmento, el negocio de préstamos multipropósito es el negocio que tiene más perspectivas de desarrollo.